Financial depth-economic growth nexus in Ukraine - Shapoval, Yuliia (PC TECHNOLOGY CENTER, 2022)
The book is devoted to the debate on the nature and direction of the relationship between financial depth and economic growth. Addressing the theoretical underpinnings of financial depth, namely the concept, measurement approaches, benefits and drawbacks, and determinants (focusing on the institutional environment) provides insights on prior studies on its relationship with economic growth before and after the GFC. This demonstrates the changes in the nature of the financial depth and economic growth nexus in the context of: the direct-proportional relationship between them, to a weakening and, in some cases, to the opposite influence. Drawing from the trends of economic development and of financial depth worldwide, distinctions across groups of countries by income and Ukraine are identified. The quantitative analysis of Ukraine's financial depth across assets, liabilities, volumes of services of non-bank and capital market, state debt and lending (of state banks, state investment projects, local loans, and cooperation with IOFs) demonstrates sectoral unbalanced financial deepening of the economy. It is grounded that financial depth, debt burden and economic growth move synchronously or in different directions based on business cycle phases. The estimation of bank loans' impact on economic growth, provided by evaluating the financial performance of Ukrainian industrial firms during 2006-2020, shows bank loans substitution by commercial (inter-firm) credit; preference for short-term loans denominated in the national currency; sufficient profitability to service loans only of mining industry firms; quasi-risky financing model. Further, the book proposes an empirical study of Ukraine's financial depth-economic growth nexus, revealing that the financial depth just accompanies economic growth but not causes it. During 2008-2020, the impact of bank and non-bank loans was negative, while the impact of trading volume on the securities market was positive, indicating the inability of further credit expansion to contribute to economic growth. Though economic growth has a directly proportionated correlation with external trade and debt, the correlation between mentioned factors and financial depth is inversely proportionate. Meanwhile, the relationship between financial openness and financial deepening in Ukraine is confirmed. The study concludes with an analysis of the impact of war on the financial depth-economic growth nexus in Ukraine. This book is a must-read for researchers, scholars, and policy-makers interested in a better understanding of the economic growth and financial development of Ukraine alike.